Complications of upper urinary system laparoscopic surgery: a single center experience with 942 cases - Ekşi, Mithat; Şahin, Selçuk; Şener, Nevzat; Şeker, Kamil Gökhan; Evren, İsmail and Karadağ, Serdar and Yavuzsan, Abdullah Hızır and Özlü, Deniz Noyan and Tuğcu, Volkan (The European Research Journal, 2021)
Objectives: Since the introduction of laparoscopic nephrectomies, laparoscopic surgeries in the field of urology have become increasingly popular. Laparoscopic surgery has its advantages but carries the risk of complications like all interventions. In our study, we aimed to discuss our complication rates according to difficulty level by presenting our experiences with urological laparoscopic procedures for the upper urinary system. Methods: This retrospective study includes 942 laparoscopic urological procedures performed by a single surgeon. The procedures divided into three groups according to the European Scoring System (ESS) Classification. The complication rate of each group was calculated separately. Results: A total of 127 (13.4%) complications were observed. Partial nephrectomy, nephroureterectomy and ureterolithotomy had the highest complication rates. Renal cyst excision, simple nephrectomy and radical nephrectomy had the lowest complication rates. According to the Clavien Complication Classification, the distributions of Grade 1, 2 and 3 complications were 29.1% (n =37), 57.4% (n = 73) and 13.3% (n = 17); respectively. The open conversion rate was 0.84%. When procedures were classified as “easy”, “difficult” and “very difficult” according to the ESS classification; complication rates were found 7.3% in the easy group, 13.3% in the difficult group and 16.6% in the very difficult group. There was no significant difference between the three groups in terms of complication rates (p = 0.329). Conclusions: Performing easier operations according to ESS in the first years of the learning curve is beneficial in preventing complications. With increasing experience, more complicated procedures can be performed with similar complication rates.